2020
DOI: 10.1093/gerona/glaa171
|View full text |Cite|
|
Sign up to set email alerts
|

Is Sensory Loss an Understudied Risk Factor for Frailty? A Systematic Review and Meta-analysis

Abstract: Abstract Background Age-related sensory loss and frailty are common conditions among older adults, but epidemiologic research on their possible links has been inconclusive. Clarifying this relationship is important because sensory loss may be a clinically relevant risk factor for frailty. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 92 publications
5
62
0
1
Order By: Relevance
“…Although this meta-analysis did not include/retrieve studies conducted in such a specific population as ours, results from our study show that people with low cognitive performance who self-reported VI were also more likely to be frail. The underlying mechanisms of the association between VI and frailty remain to be clarified [10]. Several consequences (nonexclusive) of VI such as depression, anxiety, cognitive disorders, loneliness, physical inactivity, and falls are risk factors for frailty [2,[25][26][27][28].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this meta-analysis did not include/retrieve studies conducted in such a specific population as ours, results from our study show that people with low cognitive performance who self-reported VI were also more likely to be frail. The underlying mechanisms of the association between VI and frailty remain to be clarified [10]. Several consequences (nonexclusive) of VI such as depression, anxiety, cognitive disorders, loneliness, physical inactivity, and falls are risk factors for frailty [2,[25][26][27][28].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, it is recognized that self-reported responses provide valid information about participants' perceived health and therefore have a real scientific value. Despite the fact that the accuracy of self-reported VI measurement may be discussed according to cultural and socioeconomic context [33,34], it should be noted that previous studies using both self-reported and measured VI had found significant association between VI and frailty in older people [6][7][8]10]. In addition, similar to Fried's phenotype, it has been shown that the SOF index is able to predict adverse outcomes of frailty such as falls, disability, and mortality [12,14].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deve-se ressaltar que a incapacidade comunicativa vem sendo estudada em idosos a pouco tempo, daí existirem insuficientes estudos que avaliem as necessidades específicas das pessoas idosas com DPS (Tan et al, 2020). Daí, necessidades de várias ordens, como as relativas à comunicação, à orientação, à mobilidade, ao trabalho, a atividades Research, Society andDevelopment, v. 10, n. 2, e16410212287, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i2.12287 socioculturais, ao acesso de informações sobre o que ocorre no mundo, todas essenciais para poder manter a autonomia pessoal e fazer com que esta pessoa possa continuar a sentir-se incluída no ambiente familiar e social, ainda serem pouco trabalhadas no setor saúde (Viljanen & Tormäkangas &Vestergaard, 2014).…”
Section: Discussionunclassified